Three Novel Acinetobacter baumannii Plasmid Replicase-Homology Groups Inferred from the Analysis of a Multidrug-Resistant Clinical Strain Isolated in Argentina - Cameranesi, María Marcela (2017)
Acinetobacter baumannii is an important opportunistic pathogen responsible for a variety of nosocomial infections [1,2]. Its success in the hospital environment obeys to multiple causes, among them, the ability to resist antimicrobial compounds. It can rapidly evolve Multidrug Resistance (MDR) when confronted with antibiotic therapy [1-3] and in particular, the emerging resistance to last-resort carbapenems represents a major concern worldwide [3]. The most frequent cause of carbapenem resistance in A. baumannii is represented nowadays by the acquired Carbapenem-Hydrolyzing Class D β-Lactamases (CHDL) of the OXA-23, OXA-40 and OXA-58 groups, with the respective blaOXA genes generally embedded in distinct genetic structures carried by plasmids [2,4-7].